Diversifikasi Jahe Lokal sebagai Solusi Inovatif dalam Pencegahan Stunting Melalui Kolaborasi Dengan Ibu PKK Sungai Pinang Lama [Diversification of Local Ginger as an Innovative Solution for Stunting Prevention through Collaboration with the PKK Mothers of Sungai Pinang Lama] - Tuti Alawiyah; Anita Herawati; Sari Tanjung; Nuur Dwi Hanifah; Sonia Puja Agatha; Ade Putri Maharani br Sinambela; Winda Aulia Zahra (Indonesia Berdaya, 2026)
Stunting is one of the chronic nutritional problems that remains a major challenge in rural areas of Indonesia, including in Sungai Pinang Lama Village, Sungai Tabuk Subdistrict, Banjar Regency, South Kalimantan. This condition is generally caused by limited community knowledge about balanced nutrition, restricted access to clean water, and inadequate environmental sanitation. Stunting prevention efforts need to be carried out in an integrated manner through community empowerment, particularly empowering women as the primary drivers of family welfare. Through a Community Service (PkM) program, the implementing team carried out a diversification initiative for products made from local ginger (Zingiber officinale Roscoe) as an innovative solution to improve family nutritional status while simultaneously strengthening household economies. This program was implemented in collaboration with the PKK Mothers of Sungai Pinang Lama Village using educational, training, and mentoring approaches. The activities focused on increasing knowledge of nutrition and family health, training in the production of ginger-based herbal and nutraceutical products, and developing entrepreneurship through innovation in local food products. The results showed a significant increase in partners’ knowledge, production skills, and economic independence. A total of 90% of participants experienced an improvement in understanding nutrition and stunting prevention, and were able to produce instant ginger herbal drinks and nutraceutical biscuits from ginger dregs that have high economic value. This program serves as an example of applying a scientific approach based on local wisdom to realize a healthy, productive, and self-reliant community. Abstrak. Stunting merupakan salah satu permasalahan gizi kronis yang masih menjadi tantangan utama di wilayah pedesaan Indonesia, termasuk di Desa Sungai Pinang Lama, Kecamatan Sungai Tabuk, Kabupaten Banjar, Kalimantan Selatan. Kondisi ini umumnya disebabkan oleh keterbatasan pengetahuan masyarakat mengenai gizi seimbang, akses terhadap air bersih yang terbatas, serta sanitasi lingkungan yang belum memadai. Upaya pencegahan stunting perlu dilakukan secara terpadu melalui pemberdayaan masyarakat, khususnya perempuan sebagai penggerak utama keluarga. Melalui kegiatan Pengabdian kepada Masyarakat (PkM), tim pelaksana melaksanakan program diversifikasi produk berbahan dasar jahe lokal (Zingiber officinale Roscoe) sebagai solusi inovatif untuk meningkatkan status gizi keluarga sekaligus memperkuat ekonomi rumah tangga. Program ini dilaksanakan melalui kolaborasi dengan Ibu PKK Desa Sungai Pinang Lama dengan pendekatan edukasi, pelatihan, dan pendampingan. Kegiatan difokuskan pada peningkatan pengetahuan gizi dan kesehatan keluarga, pelatihan pembuatan produk herbal dan nutraseutikal berbasis jahe, serta pengembangan kewirausahaan melalui inovasi pangan lokal. Hasil kegiatan menunjukkan adanya peningkatan signifikan dalam aspek pengetahuan, keterampilan produksi, dan kemandirian ekonomi mitra. Sebanyak 90% peserta mengalami peningkatan pemahaman tentang gizi dan pencegahan stunting, serta mampu memproduksi jamu jahe instan dan biskuit nutraseutikal dari ampas jahe yang bernilai ekonomi tinggi. Program ini menjadi contoh penerapan pendekatan ilmiah berbasis kearifan lokal dalam mewujudkan masyarakat sehat, produktif, dan mandiri.